PENINGKATAN PEMBELAJARAN IPS MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE DI SEKOLAH DASAR - Rezi, Iqbal Fahru; Harni, Harni; S, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The researchis animed to improve the students’ learning outcomes in learning the Social Study Subject by using the Cooverative Learning, Think Pair Share Model at 5th grade of SDN 05 Bandar Buat. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were teachers (practitioners) and 28 students. The result of this research shows an excalation from cycle I to cycle II on : a) planning of 7.2%, b) implementation, teacher aspect and student aspects of 19,6%, and    c) student learning outcomes of 8,7%. It can be concluded that used Cooperative Learning Model Type Think Pair Share can improve students achievement in learning social study of elementary school. Keywords :  Learning outcomes, Social study, model